PROMOTION ASSESSMENT SYSTEM / TEACHER POSITION BASED ON CREDIT FIGURES - Ridwan Hadi; Susi Wagiyati, Ir, MM (Jurnal Sistem Informasi, 1998)
Information that is accurate, precise and efficient information system is inseparable from good. And this must be supported by good data processing systems primarily utilizing the computer facilities. This computer tool can help data processing becomes faster and more efficient. But this new system is not computerized, making all the work because there are things that must remain do manually, for example, only the results of the calculation of loan rates for teachers in the office / group can not directly be automatically changed. But with this system can simplify their jobs.